2020
DOI: 10.3354/esr01026
|View full text |Cite
|
Sign up to set email alerts
|

Use of genetic mark-recapture to estimate breeding site fidelity and philopatry in a threatened sea duck population, Alaska-breeding Steller’s eiders

Abstract: The Steller’s eider Polysticta stelleri is a sea duck that breeds in Arctic tundra regions of Russia and Alaska (USA). The Alaska-breeding population is listed as ‘threatened’ under the US Endangered Species Act because of a perceived contraction of the breeding range in North America. Understanding demography of the listed population is critical for evaluating measures that can lead to increased abundance and thus, long-term viability. Specifically, estimates of return rates to breeding areas by adult females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
3
1
Order By: Relevance
“…In Arctic Canada, Arctic foxes were responsible for the majority of snow goose depredations from 1996 to 1999 and 100% of shorebird nest depredations captured on camera from 2009). Even in Utqiagvik, Alaska, where foxes were removed for predator control, Arctic foxes were still the primary egg predator of sea ducks in several years (Safine 2011. Conversely, in our camera study, we found red foxes and wolverines were responsible for most nest losses in 2017 and 2019, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…In Arctic Canada, Arctic foxes were responsible for the majority of snow goose depredations from 1996 to 1999 and 100% of shorebird nest depredations captured on camera from 2009). Even in Utqiagvik, Alaska, where foxes were removed for predator control, Arctic foxes were still the primary egg predator of sea ducks in several years (Safine 2011. Conversely, in our camera study, we found red foxes and wolverines were responsible for most nest losses in 2017 and 2019, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…While this study focused only on use of wetlands during the prenesting period, Arctophila wetlands continue to be used by sea ducks throughout the summer. Indeed, within our study area in 2011–2012, 48%–50% of locations of Steller's eider broods, and 34%–47% of spectacled eider broods, occurred within Arctophila wetlands (Safine, 2013 ). For Steller's eiders specifically, in 6 years from 1995 to 2012, 43%–85% of brood locations were in wetlands dominated by Arctophila (Safine, 2013 ).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, within our study area in 2011–2012, 48%–50% of locations of Steller's eider broods, and 34%–47% of spectacled eider broods, occurred within Arctophila wetlands (Safine, 2013 ). For Steller's eiders specifically, in 6 years from 1995 to 2012, 43%–85% of brood locations were in wetlands dominated by Arctophila (Safine, 2013 ). Thus, Arctophila wetlands provide critical resources not only for females upon arrival at the breeding grounds but also for the rearing of young.…”
Section: Discussionmentioning
confidence: 86%
“…Because Steller's eider breeding is rare on the YKD, no comparable information is available although Flint and Herzog (1999) did document a single female that returned to breed in multiple years. Further, analyses by Safine et al (2020) suggest breeding site fidelity and moderate to high degree of natal philopatry for Steller's eiders near Utqiagvik, Alaska. In the U.S., the spectacled eider was listed as threatened by the U.S.…”
Section: Introductionmentioning
confidence: 98%